First Isolation of Candida nivariensis, an Emerging Fungal Pathogen, in Kuwait - Alobaid, Khaled (Med Princ Pract, 2021)
OBJECTIVE: C. nivariensis is a rare Candida species which is phenotypically closely related to Candida glabrata and Candida bracarensis. The 3 species form the C. glabrata sensu lato complex. Here, we describe the first isolation and characterization of a C. nivariensis isolate cultured from the tracheal aspirate obtained from a young man in Kuwait. MATERIALS AND METHODS: The yeast isolate was initially tested by VITEK 2 followed by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) and multiplex PCR. The identification was confirmed by sequencing of internal transcribed spacer (ITS) region of rDNA. Antifungal susceptibility testing was performed by Etest, and phylogenetic comparison with other international strains was carried out by using MEGA version 7 software. RESULTS: The C. nivariensis isolate was misidentified by VITEK 2, but correctly identified by MALDI-TOF MS with updated software and multiplex PCR. The identity was confirmed by sequence comparisons of ITS region of rDNA. Antifungal susceptibility testing revealed high minimum inhibitory concentration (MIC) against fluconazole, but low MICs against amphotericin B and echinocandins. Phylogenetically, our isolate was closely related to Indian isolates. CONCLUSIONS: This report extends the geographic distribution of C. nivariensis to the Arabian Peninsula. MALDI-TOF MS with updated software and molecular tests are needed to correctly identify C. nivariensis. Since C. nivariensis may exhibit reduced susceptibility to antifungal agents, accurate identification and antifungal susceptibility testing are essential, particularly for isolates from sterile sites, for optimal patient management.